Construction of Elementary School Students' Interest in Traditional Arts in Arts and Culture Learning - Hepi Dwi Surya; Syahran Syahran; Heroza Firdaus (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to deeply understand elementary school students’ interest in traditional arts at SD Negeri 11/VII Lubuk Kepayang. This research employs a qualitative approach using a case study design. The subjects include fourth, fifth, and sixth grade students, as well as teachers and parents as supporting informants. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that students’ interest in traditional arts is shaped through direct experiences in classroom learning, extracurricular activities, and social support from teachers, peers, and families. However, this interest still faces several challenges, including limited facilities, the dominance of modern popular culture, and lack of exposure to traditional art practices. In conclusion, students’ interest in traditional arts is influenced by both internal and external factors. Therefore, contextual, participatory, and sustainable learning str ategies are needed to enhance students’ engagement with local culture